Control of Turbulence in a Multiple-Fan Wind Tunnel: Part5, Reproduction of Spatial Structures in an Atmospheric Boundary Layer - OZONO, Sigehira; NISHI, Akira; MATSUDA, Yuji; MIYAGI, Hiromori; KIKUGAWA, Hironori; HIRANO, Kimitaka; CAO, Shuyang (Journal of Wind Engineering, 2000)
Multiple-fan wind tunnels have been developed in our laboratory to investigate the effects of turbulent wind on large structures, such as high-rise buildings, long-span suspension bridges, etc.. In the previous report, coherence of turbulence between laterally separated points as well as many other statistical parameters, was reproduced in the tunnel by assuming a randomly distributed phase-lag. The vertical profiles of the coherence, the phase-lag and cross-correlation coefficient in an atmospheric boundary layer were investigated and presented in this paper. First, target of these parameters were determined by analyzing observed data on a meteorological tower. Second, the reproduction of these parameters was examined in the methods of numerical simulation and experiment in the wind tunnel. As the result, the profiles of these parameters were obtained closely to each target.